Is there a relationship between ocular discomfort and circulating plasma levels of sex hormones? Preliminary findings - Blanka Golebiowski, Blanka; Hampel, Ulrike; Badarudin, Noor Ezailina; Jalbert, Isabelle; Madigan, Michele; Stapleton, Fiona (Association for Research and Vision Ophthalmology, 2013)
Purpose: Dry eye is a common problem especially for women post-menopause. This study explored the relationship between circulating levels of plasma sex hormones and ocular dry eye symptoms. Methods: A cross-sectional, single visit study was conducted. The study involved a convenience sample of 74 subjects without ocular surface disease, including 52 females (mean age 35.3±13.4years, range 18.8-70.3) and 22 males (mean age 34.2±13.8years, range 20.2-75.3). Subjects completed the Dry Eye Questionnaire (DEQ5) and numerical ratings of discomfort, dryness, foreign body (FB) sensation, burning and watering. Tear osmolarity (TearLab) and volume (Phenol Red Thread) were assessed. Venous blood was collected and plasma concentrations of oestradiol (E2) and total testosterone (TT) were determined using specific Enzyme-linked immunosorbent assay. Associations were examined using Pearson’s or Spearman’s correlations, and differences between groups were assessed using Independent samples t-test or Mann-Whitney U test, as appropriate. Results: Mean group E2 concentration was 65.2±50.9pg/ml in females and 40.7±23.8pg/ml in males; TT concentration was 0.49±0.29 and 4.3±1.6ng/ml respectively. All symptoms measures were higher in females (p<0.05). Tear volume was reduced in females (p=0.02); there was no difference in tear osmolarity. In females, increased ocular symptoms correlated with higher levels of E2 (DEQ5 Rho=0.36, p=0.01; dryness Rho=0.36, p=0.01; FB Rho=0.37, p=0.01). Higher TT in females correlated with more FB sensation (Rho=0.30, p=0.03) and lower tear volume (Rho=-0.30, p=0.04). No association was found between tear osmolarity and hormone levels in females. In males, no evidence of a relationship between hormone levels and ocular symptoms or tear parameters was apparent. Although concentrations of E2 and TT were reduced with age in females (E2 Rho=-0.36, p=0.01; TT Rho=-0.37, p=0.01), there was no association between age and ocular symptoms in either males or females. Conclusions: Higher circulating levels of sex steroid hormones appear to play a role in increased symptoms of dry eye in females without ocular surface disease, but not in males. This effect does not appear to be influenced by age. More detailed analysis and exploration of co-related factors such as levels of free testosterone is warranted to further explore these relationships in the pathophysiology of dry eye.